Pandangan Ulama Konservatif dan Ulama Progresif tentang Tafsir Ayat Lâ Ikrâh fî al-Dîn - Abd Moqsith (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2013)
The verse Lâ Ikrâh fî al-Dîn has been one of the most contested verses with regard to its meaning and definition by the ulama (religious scholars) from the past to the present. Basing on this verse, progressive ulama maintain that the idea of freedom of religion introduced by modern society does not contradict the Qurân. For them, freedom of religion includes not only freedom to convert to Islam, but also freedom to convert from Islam. This view is rejected by conservative ulama who argue that the meaning of the verse contains only freedom to convert to Islam, not to convert from Islam. If non-Muslims are free to convert to Islam, Muslims are not allowed to convert from Islam. Moreover, there are many ulama who argue that the verse has been abrogated by other tens of verses which enjoin to fight against infidels and polytheists. After the revelation of verses of war? in the Qurân, the verse Lâ Ikrâh fî al-Dîn becomes no longer legally binding.